ANALISI HUKUM ISLAM TERHADAP PEREMPUAN YANG MENIKAH DALAM MASA IDDAH - NIM A1011201321, MASYITOH RAMADANI (Fakultas Hukum Universitas Tanjungpura, 2024)
AbstractMarriages during the iddah period generally have the potential to cause legal problems. Marriages that occur before the waiting periode ends can have an impact on the validity of the marriage. However, dispite causing legal problems, the practice of marrying prospective brides during the iddah period still occurs in Indonesia. The calculation of court settlement time is a calculation that can be legally recognized. This thesis is entitled